Representasi Komunikasi Persuasif Pelatih American Football Terhadap Team - Aldi Azis; Mochammad Rochim (UNISBA Press, 2023)
Abstract. In general, every human being often communicates in his daily life, using various types, messages, and media. There are several types of communication, one of which is persuasive communication, which aims to adapt someone in order to increase people's motivation and encouragement to achieve a goal. Persuasive communication can be used not only when speaking, but also in any situation where a person has a goal and wants to urge others to help him achieve that goal, as the coach does with his team that has won every game. The purpose of this research is to know the meaning of denotation, connotation, and myth of the persuasive communication form of American Football coach in the movie